2023
DOI: 10.1186/s13102-023-00667-7
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of foot intensive rehabilitation (FIRE) on clinical outcomes for patients with chronic ankle instability: a randomized controlled trial protocol

Abstract: Background Lateral ankle sprains account for a large proportion of musculoskeletal injuries among civilians and military service members, with up to 40% of patients developing chronic ankle instability (CAI). Although foot function is compromised in patients with CAI, these impairments are not routinely addressed by current standard of care (SOC) rehabilitation protocols, potentially limiting their effectiveness. The purpose of this randomized controlled trial is to determine if a Foot Intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors identified an omission in the current competing interests section. The competing interests should read as follows:…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an omission in the current competing interests section. The competing interests should read as follows:…”
mentioning
confidence: 99%